Aadhaar: Uniquely Indian Dystopia? - Reetika Khera (economic sociology_the european electronic newsletter, 2019)
On 28 January 2009, the Government of India constituted the Unique Identification Authority of India (UIDAI) through a Gazette notification. The main aim was to "generate and assign UID to residents", where UID refers to "Unique Identity". The brand name "Aadhaar" (meaning "foundation" in some Indian languages) and a logo followed. The Aadhaar project came to be seen as one of the flagship schemes of the second United Progressive Alliance (UPA-2) government (2009-2014).
Keywords: 300